Electrochemical Oxidation and Speciation of Lanthanides in Potassium Carbonate Solution. Issue 4 (1st April 2022) - Tse, Poki; Bessen, Nathan P.; Galley, Shane S.; Bryan, Samuel A.; Lines, Amanda M.; Shafer, Jenifer
Abstract : Increasing lanthanide demand to support clean energy goals drives the need to develop more efficient approaches to separate adjacent lanthanides. Most approaches for lanthanide separations are not very selective and are based on small differences in lanthanide ionic radii. Concentrated potassium carbonate media has shown some potential to enable oxidation of praseodymium (Pr) and terbium (Tb) to their tetravalent states, which could ultimately enable a separation based on differences in oxidation states, but very little is known regarding the system's chemistry. This work completes a detailed examination of cerium (Ce) redox chemistry in concentrated carbonate media to support the development of Pr and Tb oxidation studies. The half-wave potential (E1/2 ) of the Ce(III)/(IV) redox couple is evaluated under various solution conditions and computational modeling of carbonate coordination environments is discussed. Cyclic voltammetry shows higher carbonate concentrations and temperatures can lower the potential required to oxidize Ce(III) by 54 mV (3.5 to 5.5 M) and 39 mV (from 10 °C to 70 °C). Chronoabsorptometry shows Ce(III) and Ce(IV) carbonate complexes are chemically stable and reversible. Computational modelling suggests the most likely coordination environment for the Ce(IV) complex is Ce(CO3 )4 (OH) 5− which is less entropically favorable than the lowest energy Ce(III) complex, Ce(CO3 )4 5− .